Percepções dos alunos sobre sua própria (des) motivação: estudo comparativo em turmas dos cursos extensivo e intensivo de licenciatura em letras língua inglesa - SOUZA, Marcus Alexandre Carvalho de (Universidade Federal do Pará, 2015)
Not only motivation but also its opposite – demotivation – have been studied in the scope of foreign languages learning. However, only a few works investigate these constructs in the point of view of their dynamicity. This research aims at comprehending motivation and demotivation in two groups of undergraduate students of a Teaching English as a Foreign Language Program - one extensive class and one intensive class – and the implication of these constructs in the learning of the target language. Using theoretical principles established by Dörnyei and Ushioda (2011), Dörnyei (2011, 2001), Ushioda (2008), Gardner (2007), Deci and Ryan (2000) among others, data collected through a questionnaire and the academic transcripts of the students from both classes were analyzed. The research is a case study, which uses the comparative method. The research took place at the Federal University of Pará, Bragança Campus, and has 21 participants: 11 students from the extensive class and 10 from the intensive class. Although there are motivational patterns that group some students, motivation was perceived as individual and changing, since the motivational process does not happen in the same manner, exerts diverse influences in different subjects, and even changes over time in one individual. The data also shows the complexity of the construct, since the existence of motivation does not mean that negative influences could not occur, as well as that negative influences can enhance a later motivational increase. In addition, it was noticed that motivation perceived by these students does not assure good outcomes in the subjects they were studying. This research can help in the comprehension of the motivational process as a dynamic system, and to understand that both students from extensive or intensive classes can be motivated, since motivation is an individual condition.